Heart rate running speed relationships during exhaustive bouts in the laboratory - Boudet, G.; Albuisson, E.; Bedu, M.; Chamoux, A. (Canadian Journal of Applied Physiology, 2004)
The present study was designed to investigate the heart rate-running speed (HR-RS) relationship while exercising continuously, at high intensities, on a treadmill. The purpose was to precisely measure the magnitude of drop in RS necessary to maintain HR during intense exhaustive exercises, and to determine whether the magnitude of drop in RS is directly depedent on exercise intensity. Sixteen male endurance athletes performed five treadmill tests: an incremental test for maximal O2 uptake and maximum aerobic velocity (VMA), and four exhaustive tests: at 82, 86, 89, and 92% VMA. After an adaptation period of 3 min, the objective was to stabilise HR by adjusting the treadmill speed continuously by ± 0.5 km·h-1 every 30 sec. Attained intensities were: 82% (±6), 84% (±6), 89% (±3), and 90% (±6) VMA, respectively [L1, L2] vs. [L3, L4], p < 0.05. Time to exhaustion accross the increasing intensities, respectively, were: 36.58 (±4.45), 24.63 (±3.25), 15.80 (±2.00), and 9.87 (±1.15) min, p < 0.05, with the exception of L3 vs. L4. The RS/HR ratio vs. speed showed three phases: an increasing adaptive (AB) phase 0-165 sec with an averaging maximal level of 1.67 m·beat-1 at 165 sec, a transitional period 170-245 sec, and a decreasing (BC) phase 250-1800 sec with a lower level of 1.29 m·beat-1at 1800 sec. In our experimental conditions, for high intensities 82 to 90% VMA, cardiac drift which disturbed the RS-HR relationship with duration was evaluated: -0.143 km·h-1 per minute for HR stabilisation. This cardiac drift is a linear function of time. Results suggest that HR and RS are not interchangeable variables for this kind of exercises, and it seems more reliable to gauge exercise intensity using RS than HR.